Religiosity as a subject of study (Eurasian Research Bulletin, 2022)
This article is devoted to the philosophical analysis of religiosity in the modern conditions of the information society, the need for which is due to a new religious boom or renaissance in the CIS countries, as well as the evolution of the Muslim image and way of life. The authors attempt to interpret the originality and features of the religiosity of Muslims in the light of democratic changes regarding the right to religiosity in the context of conservatism and liberalism. Religiosity in its essence. is the basis of the right to freedom of conscience, that citizens have the right to meet religious needs, as well as the rejection of religiosity, the conduct of a scientific and rationalistic way of life. The authors consider the manifestation of the main forms and qualities of religiosity, in particular modern forms of religiosity of youth on the basis of sociological research data among the population of the CIS countries. The religiosity of Muslims is a special "caste" of believers, different from other faiths, implying voluntary faith, confirmation and recognition of Allah as the king of the Universe, living according to the rules of Islam, obeying the instructions and requirements of the Muslim community. The true norms of sacred norms call all to the humanistic principles of wassatiya as a moderate shackle of religiosity, without going to extremes. The authors are inclined to believe that the consolidation of all creative forces of the world community for the dissemination of new standards of tolerance, which implies the readiness of peaceful coexistence for the benefit of man. In turn, the religiosity of citizens allows them to profess any religion or not to profess any, and forced conversion to one or another religion is also prohibited. Religiosity is a universal human norm of socio-cultural life, a natural human right